The legal nature of corporate disputes - Alexeyeva S.V. (Хабаршы. Заң сериясы, 2017)
The article considers the legal nature of corporate disputes. The author gives the definition of the concepts of «corporate conflict» and «corporate dispute» with the latest changes in procedural law, resulting in a general characterization of regulatory proceedings in corporate disputes.